Effect of Designed Learning Package on Teaching: a Case Study - Naderi, Maryam (International Journal of Bio-resource and Stress Management, 2023)
Learning package is one of the most notable solutions to go with the global evolution and produce the proper environment for teaching and learning. An attempt was made to investigate the effect of learning package on psychology and moral of the students and thereby in the improvement of the educational environment. The study was carried out in two main steps- preparing the learning package considering the current situation and studying the effect of learning package on psychology, moral and educational improvement of the students. A practical package was prepared for the sample region using questionnaire. The sample group was provided with the learning package. Using pre and post-test from the sample group, the educational improvement was investigated and the effect of the package on psychology and moral feelings of the group was examined using the questionnaire. The results showed that the prepared learning package suits and works for the study region. There is also notable progress in psychological, moral and educational improvement of the students.